Impact of new technologies and artificial intelligence in brand management - Dobreva, Alena (Yearbook Telecommunications, 2024)
The topic of this article was chosen due to its relevance and the opportunity to explore various aspects of new technologies and artificial intelligence (AI) in marketing and customer service. Brand management plays a crucial role in modern business, as building, maintaining and developing a brand is essential for attracting and retaining customers. However, the integration of AI also raises important concerns about privacy, transparency and social responsibility, which are crucial for maintaining consumer trust. The article aims not only to show the innovative potential of AI, but also to highlight its role in building sustainable and successful brands. Existing practices are analyzed, as well as new opportunities that can be implemented as the technology continues to develop, the challenges and limitations of artificial intelligence, the risks and limitations associated with AI are examined, emphasizing the balance between automation and maintaining an emotional connection with customers.